The reproductive biology, population dynamics, production and fishery of the freshwater clam Galatea paradoxa (Born, 1778) in the Volta river, Ghana. - Adjei-Boateng, Daniel (Trinity College (Dublin, Ireland). Department of Zoology, 2010)
The reproductive biology, population dynamics and production of Galatea paradoxa (Bom 1778) (Donacidae) which is the basis of an artisanal fishery at the Volta River Estuary, Ghana, was studied from March 2008 to February 2010. Histological observation of the gonads revealed that G. paradoxa is gonochoristic with a dominance of females (80%) and a high incidence of hermaphrodites (9.4%). The reproductive cycle is annual with a single spawning event between July and October. Gametogenesis starts in December and progresses steadily to a peak in June-July when spawning begin until November when the animals are spent. Condition and gonadal indices showed a clear relationship with the gametogenic stages rising from minimum values in stage (I) at the start of gametogenesis to maximum values at stages (IIIA) ripe and (IIIB) start of spawning (June - August) before declining significantly to minimum values in stage (IV) spent.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin